Sensitivity of notochordal disc cells to mechanical loading: an experimental animal study - Gühring, Thorsten; Nerlich, Andreas; Kröber, Markus; Richter, Wiltrud; Omlor, Georg (European spine journal, 2010)
The immature disc nucleus pulposus (NP) consists of notochordal cells (NCs). With maturation NCs disappear in humans, to be replaced by chondrocyte-like mature NP cells (MNPCs); this change in cell phenotype coincidences with early signs of disc degeneration. The reasons for NC disappearance are important to understand disc degeneration, but remain unknown, yet. This study investigated, whether loading induced a change from a notochordal nucleus phenotype to a chondrocyte-like one. An in vivo disc compression model with fixateur externe was used in 36 mature rabbits. Discs were compressed for different time periods (1, 28, 56 days), and compared with uncompressed control discs (56 days without treatment), and discs with sham compression (28 days). Nucleus cell phenotype was determined by histology and immunohistochemistry. NCs, but not MNPCs highly expressed bone-morphogenetic-protein 2 and cytokeratin 8, thus NC and MNPC numbers could be determined. A histologic score was used to detect structural endplate changes after compression (28 days). Control and sham compressed discs contained around 70% NCs and 30% MNPCs, to be decreased to <10% NCs after 28-56 days of loading. NC density fell sharply by >50% after 28-56 days of compression (P < 0.05 vs. controls). Signs of decreased endplate cellularity and increased endplate sclerosis and fibrosis were found after loading. These experiments show that NCs were less resistant to mechanical stress than MNPCs suggesting that increased intradiscal pressures after loading, and limited nutrition through structurally altered endplates could instigate the disappearance of NCs.